Investigating the Use of Communicative Language Teaching (CLT) Strategies to Promote Innovative Teaching and Learning Approach - Jaslie S. Sitoy; Ramir Philip Jones V. Sonsona (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
English learners from the Philippines also face difficulties in learning English. Even though most Filipinos have some level of fluency in English, a gradual decline can be observed based on the EF English Proficiency Index (annual ranking based on their level of English proficiency) over the past few years. This research investigates using communicative language teaching (CLT) strategies to promote innovative teaching and learning approaches. This research uses a qualitative descriptive method using a Focus Group Discussion (FGD) approach. Data collection methods use interviews, document recording, and questionnaires. The data collection instrument uses a questionnaire sheet. The data analysis technique uses qualitative descriptive analysis techniques. The results of the study revealed that SHS teachers' use of CLT is evident in their encouragement of practical language use and engaging students in communicative activities such as role-playing and opinion sharing, in line with existing research that highlights the efficacy of the approach in improving students' communication skills, critical thinking and acquisition of vocabulary. This study noted variations in CLT implementation among teachers, indicating the need for further professional development and support to ensure consistent and practical application of CLT principles, ultimately benefiting student learning outcomes.